STUDI KOMPARASI INSTAD DIPADU MIND MAP DENGAN PEMBELAJARAN KONVENSIONALTERHADAP KEMAMPUAN BERPIKIR ANALITIS BIOLOGISISWA KELAS XI IPA SMAN 4 SURAKARTA - Utami, Yekti Nur; Probosari, Riezky Maya; Sugiharto, Bowo (Universitas Sebelas Maret, 2013)
This research is aimed to compare the two models; INSTAD supported by mind map visualization and the conventional teachered center in term of their capabilities in improving student’s analytical thinking.Quasy experimental paradism of research is followed with Posttest Only with Non-equivalent Groups Design. The population in this research was all of the student at the XI Science Class in SMA N 4 Surakarta, at the academic year of 2012/2013. The whole population consist of 188 students that are dispersed within 6 classes. Samples are taken in a group of student (cluster sampling method). The data are collected upon the samples taken using the instrument sheet of examining the analytical thingking capability.The result shows that the mean value of the analytical thingking in the experimental group (74,00) is greater than in the comparison one (60,63). The learning in experimental group using INSTAD supported by mind map could practice the student’s cognitive skill so that the student’s analytical thinking competence could develop. It could not be found in the control group which the learning use conventional method. It can be concluded that INSTAD supported mind map visualization is better than conventional teachered center learning. Keywords: INSTAD, Mind Map, Biological Analytical Thinking Competency